1982
DOI: 10.1177/030098588201900111
|View full text |Cite
|
Sign up to set email alerts
|

Acute Encephalitis and Hydrocephalus in Dogs Caused by Canine Parainfluenza Virus

Abstract: Abstract. Gnotobiotic puppies were inoculated intracerebrally with a strain of canine parainfluenza virus . Four of eight dogs developed histological evidence of acute encephalitis. Clinical signs of encephalitis were seen in two of these four dogs; one had signs and lesions of interstitial pneumonia. Of six inoculated dogs observed for six months after infection, five developed internal hydrocephalus. Virus was reisolated from two dogs with acute encephalitis but not from dogs with hydrocephalus. Hemagglutina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…In dogs, SV5 commonly causes minor respiratory tract infections, although the virus has also been recovered from the cerebrospinal fluid of a dog v~ith temporary posterior paralysis (Baumgartner et al, 1981). This particular isolate has subsequently been shown to cause experimentally induced encephalitis when inoculated into gnotobiotic dogs (Baumgartner et at., 1982). Because SV5 commonly infects dogs the virus is usually referred to in veterinary circles as canine parainfluenza virus.…”
Section: Introductionmentioning
confidence: 99%
“…In dogs, SV5 commonly causes minor respiratory tract infections, although the virus has also been recovered from the cerebrospinal fluid of a dog v~ith temporary posterior paralysis (Baumgartner et al, 1981). This particular isolate has subsequently been shown to cause experimentally induced encephalitis when inoculated into gnotobiotic dogs (Baumgartner et at., 1982). Because SV5 commonly infects dogs the virus is usually referred to in veterinary circles as canine parainfluenza virus.…”
Section: Introductionmentioning
confidence: 99%
“…During the course of studying the CPIϩ virus, a derivative of CPIϩ, termed CPIϪ, was isolated from a dog that was experimentally infected with the CPIϩ virus (2). It was found that there are differences among the V/P genes of CPIϩ, CPIϪ, and the commonly used lab strain W3A, in addition to differences in other viral genes (4,5,35).…”
mentioning
confidence: 99%
“…Cells were cultured in 25 and 75cm 2 flasks and maintained in Eagle's MEM with Earle's salts, supplemented with 10% fetal calf serum and antibiotics as described [4]. The primary brain cell cultures were co-cultivated with African green monkey kidney (Veto) cells 12 (dog 1), 13 (dog 3), and 18 (dog 2) days after seeding.…”
mentioning
confidence: 99%